Exploring the potential of tree-ring chronologies from the Trafoi Valley (Central Italian Alps) to reconstruct glacier mass balance - G. Leonelli; M. Pelfini; P. Cherubini (Boreas, 2008)
Two tree-ring chronologies of stone pine (Pinus cembra L.) and two of Norway spruce (Picea abies Karst.) were constructed on the basis of data from three high-altitude sites in the Trafoi Valley (Central Alps, Italy) to test tree species sensitivity to climate at different sites and to explore the potential of the two species for reconstructing the mass balance of two glaciers in the same region (the Careser and Hintereis glaciers). Influence of climate on treering growth and on glacier mass variations was tested by means of Pearson’s correlation and response functions. At highest altitude sites, both species appeared to be sensitive to July temperatures, while stone pine also showed higher sensitivity than Norway spruce to previous winter precipitation. Comparing the dendrochronological and glaciological series, stone pine showed higher negative correlations with glacier mass balance series than Norway spruce. These different relationships reflect different species responses to climate, and stone pine is potentially useful in reconstructing past glacier mass balance in the Central Alps. Extreme climatic events induce different and even contrasting responses of tree-ring growth and glacier mass variations and may therefore bias tree-ring-based glacier mass balance reconstructions.